Raising the scale of micro urban agriculture in a socialized housing community an applied, participatory research - Santos, Julieta L. (Quezon City College of Architecture, University of the Philippines Diliman, 2010)
For many years, urban agriculture generates a lot of interest among various sectors of the society, as it shows promising potential for urban regeneration and for helping the urban sector mitigate many of its problems. Landscape architects are among many who take interest in the benefits derived from urban agriculture. While engaged in a very broad range of professional practice, one area of work landscape architects normally perform in large and small urban regeneration projects. The concept of urban agriculture is very appropriate in this type of projects, which makes it very appealing to the landscape architecture practice, as well. This study proposal delved into the integration of landscape architecture principles in the application of micro urban agriculture in a socialized housing community in Quezon City. The basic idea was to study the application of a landscape architecture-enhanced micro urban agriculture in an urban poor community. This is an applied, participatory research with the goal of evaluating the advantage of landscape architecture-enhanced implementation of micro urban agriculture in a socialized housing environment.
Vita.
Thesis (Master of Tropical Landscape Architecture)--University of the Philippines, Diliman.
Keywords: Urban landscape architecture; Urban agriculture; Urban beautification